2019
DOI: 10.1021/acs.langmuir.9b00081
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Linear to Circular Motion in Active Spherical-Cap Colloids

Abstract: Nonspherical self-propelling colloidal particles offer many possibilities for creating a variety of active motions. In this work, we report on the transition from linear to circular motion of active spherical-cap particles near a substrate. Self-propulsion is induced by self-diffusiophoresis by catalytic decomposition of hydrogen peroxide (H2O2) on one side of the particle. Asymmetric distribution of reaction products combined with the asymmetric shape of the particle gives rise to two types of motions dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…The average period of the circular trajectory for a particle is hTi ¼ 1.33 s (see Supplemental Material, I [47]). This circular trajectory is similar to the trajectories obtained with asymmetric [48][49][50] or symmetric [51] particles and in simulations of selfpropelled particles with an added torque [16,[19][20][21]23]. Figure 1(b) shows a second trajectory for the same righthanded particle guided by the wall in a counterclockwise surface mode.…”
Section: Sorting and Extraction Of Self-propelled Chiral Particles By Polarized Wall Currentssupporting
confidence: 78%
“…The average period of the circular trajectory for a particle is hTi ¼ 1.33 s (see Supplemental Material, I [47]). This circular trajectory is similar to the trajectories obtained with asymmetric [48][49][50] or symmetric [51] particles and in simulations of selfpropelled particles with an added torque [16,[19][20][21]23]. Figure 1(b) shows a second trajectory for the same righthanded particle guided by the wall in a counterclockwise surface mode.…”
Section: Sorting and Extraction Of Self-propelled Chiral Particles By Polarized Wall Currentssupporting
confidence: 78%
“…Prior works similarly report decreases in τ R and its invariance with fuel concentration. [ 58–60 ] Notably, Dietrich et al. [ 59 ] reported τ R for PS‐Pt JMs was invariant of fuel concentration, but that the change in τ R upon fuel addition was dependent on the swimming environment.…”
Section: Resultsmentioning
confidence: 99%
“…One such study showed that L-shaped particles exhibit circular trajectories. 22 More recent experiments on select anisotropic shapes or patches confirmed some of the predictions in 2D [23][24][25][26] and found unexpected motion patterns such as non-cylindrical helices 27 in 3D. Still, the current limitations in particle design prevent a systematic comparison with theory.…”
Section: Introductionmentioning
confidence: 88%